The Legal Protection of Fiduciary Guarantee Recipients & Resolution of Tort Disputes in the Fiduciary Guarantee Agreement at PT Astrido Pacific Finance - Indah Pratiwi Widyaningrum (JURNAL AKTA, 2023)
This research aims to examine the legal protection mechanism for recipients of fiduciary guarantees, such as PT Astrido Pacific Finance, in their business practices and to analyze the mechanism for resolving default disputes that can arise in fiduciary guarantee agreements. This research uses normative juridical research methods with a descriptive approach. The data used is secondary data consisting of primary and secondary legal materials. The results of this research show the importance of clarity in laws and regulations related to fiduciary guarantees to provide strong legal protection for recipients of fiduciary guarantees. In addition, a good understanding of the mechanism for resolving default disputes is needed to maintain stability and fairness in fiduciary transactions. It is hoped that the results of this research will provide guidance for PT Astrido Pacific Finance and contribute to the development of legal science in Indonesia.